Accidental Archaeologists: True Stories of Unexpected Discoveries - Sarah Albee (Bharat Scholastic, 2020)
Science meets real-life mystery in this adventurous look at incredible unexpected finds that changed history. Secret treasures are buried all around us -- you just have to look for them! Accidental Archaeologists takes you on an adventure through time to relive some of the coolest surprise discoveries by totally ordinary people all over the world. The cowboy who found an ancient skeleton- A famous king buried underneath a parking lot- The team who found New York City's hidden African Burial Ground- A boy who finds the Dead Sea Scrolls while looking for his lost goat- And many more.Packed with incredible stories and expert tips for making your own exciting finds, this is an accessible, action-packed introduction to the world of archaeology.
Keywords: Ancient History -- Ancient History; Archaeology -- Archaeology